NONEPILEPTIC SEIZURES IN PATIENTS WITH REAL DIAGNOSTED EPILEPSY - A. E. Dubenko; T. A. Litovchenko (Эпилепсия и пароксизмальные состояния)
Abstract: the analyze of 463 patients showed, that 121 patients with decompensate or ubcompensated epilepsy had nonepileptic ictuses. These patients had conversional ictuses, syncope, panic attacks, paroxysmal abstinantive states. Long turn epilepsy can be the reason for development nonepileptic seizures can worst clinical state of patients. Sometime appearing of nonepileptic seizures in epilepsy patients made diagnosis «epilepsy» doubtful. This fact was the reason for AED refused. When we diagnose the t ype of epileptic seizure, especially in-patients without good seizure control, we must remember about high probability of combi-nation epilepsy with nonepileptic seizures.